Surge in global metal mining threatens vulnerable ecosystems. (July 2021) - Luckeneder, Sebastian; Giljum, Stefan; Schaffartzik, Anke; Maus, Victor; Tost, Michael
Graphical abstract: Highlights: We perform a global, fine-grained assessment of mining trends across 3, 000 mines. Extraction of nine major metal ores increased significantly since 2000. Surge in mining occurred particularly in ecologically vulnerable regions. Limiting mining impacts demands a multilevel and supply-chain-wide approach. Abstract: Mining activities induce profound changes to societies and the environment they inhabit. With global extraction of metal ores doubling over the past two decades, pressures related to mining have dramatically increased. In this paper, we explore where growing global metal extraction has particularly taken effect. Using fine-grain data, we investigate the spatial and temporal distribution of mining of nine metal ores (bauxite, copper, gold, iron, lead, manganese, nickel, silver and zinc) across approximately 3, 000 sites of extraction worldwide between 2000 and 2019. To approach the related environmental implications, we intersect mining sites with terrestrial biomes, protected areas, and watersheds categorised by water availability. We find that 79% of global metal ore extraction in 2019 originated from five of the six most species-rich biomes, with mining volumes doubling since 2000 in tropical moist forest ecosystems. We also find that half of global metal ore extraction took place at 20 km or less from protected territories. Further, 90% of all considered extraction sites correspond to below-average relative water availability, with particularly copper and gold mining occurring in areas with significant water scarcity. Our study has far-reaching implications for future global and local policy and resource management responses to mitigate the negative effects of the expected expansion of metal mining.